Engineering Malaysia’s competitive edge: prompt engineering as critical skill for future workforce development - Osman, Fairul Nazmie; Mohd Yassin, Ihsan; Baharom, Rahimi; Abdul Aziz, Mohd Azri; Taib, Mohd Nasir (UiTM Press, 2025)
As AI technologies, especially AIs (Large Language Models, LLMs)—reshape global economies, Prompt Engineering (PE) is emerging as a vital skill for effective human-Artificial Intelligence (AI) collaboration. This paper positions PE as a strategic competency for Malaysia’s workforce development, mapping it to Bloom’s Taxonomy and identifying core skills such as language proficiency, creativity, critical thinking, and interdisciplinary knowledge. It examines implementation pathways across Malaysia’s K–12 and tertiary education systems, highlighting challenges including digital divides, educator readiness, and sociocultural norms common in Asian contexts— such as deference to authority and aversion to questioning—that hinder the development of inquiry-based skills essential for effective PE. By analyzing international benchmarks and Malaysia’s unique educational and cultural landscape, the paper argues that integrating culturally contextualized PE into national curricula is essential to democratize AI literacy, bridge skill gaps, and position Malaysia competitively in the AI-driven global knowledge economy.